A comparison of assisted human reproduction (AHR) regulation in Ireland with other developed countries - Olivia McDermott; Lauraine Ronan; Mary Butler (BMC, 2022)
Plain language summary Ireland is one of the only European countries without any form of assisted human reproduction specific regulation. This research aimed to review of assisted human reproduction regulations to compare Ireland with other developed countries. There is no assisted reproduction legislation in any country that can be described as perfect. The UK's legislation combined with the Netherlands financial legislation section is concluded as being most effective hybrid model of best practice for adoption in Ireland. It was concluded that significant changes need to be made to the Irish draft legislation which is in limbo with the government for the last 3 years.